Prevalence of syphaciosis in laboratory rodents with emphasis on species identification, treatment and Th2 cytokine response - SUNDAR, S T BINO; HARIKRISHNAN, T J; LATHA, BHASKARAN RAVI; KUMAR, T M A SENTHIL; RAMESH, S; SRINIVASAN, M R; AZHAHIANAMBI, P; GOMATHINAYAGAM, S; RAMAN, M; TIRUMURUGAAN, K G; PANDIAN, SERMA SARAVANA (The Indian Journal of Animal Sciences, 2018)
Prevalence of syphaciosis (pinworm infection) in laboratory rats and mice, species identification, chemotherapy with ivermectin and its effect on pinworm infection, and Th2 cytokine response was studied. Using perianal tape test examination, the highest rate of pinworm infection was found in male Wistar rats (69.44%) followed by female Wistar rats (62.50%), male Balb C mice (60.60%), female Swiss Albino mice (51.42%), male Swiss Albino mice (33.33%) and female Balb C mice (32.69%). Wistar rats had maximum infection (65.97%) followed by Balb C mice (46.64%) and Swiss albino mice (42.37%). Overall, males had higher infection (54.45%) compared to females (48.87%). Syphacia obvelata in mice and S. muris in rats were the pinworms identified morphologically and confirmed with polymerase chain reaction and sequencing. No mixed infection was found in rats and mice. Ivermectin (2.5 mg/kg) as oral gavage as well as in drinking water continuously for five days was highly effective in eradicationof pinworms in rats and mice. Down regulation of Th2 cytokines, viz. IL4, IL5 and IL13 was observed after ivermectin treatment in both male and female Wistar rats.